Hybridizing cost saving with trust for blockchain technology adoption by financial institutions - Ullah, Nazir; Al-Rahmi, Waleed Mugahed; Alfarraj, Osama; Alalwan, Nasser; Alzahrani, Ahmed Ibrahim; Ramayah, T.; Kumar, Vikas (Telematics and Informatics Reports, 2022)
Distributed Ledger Technology (DLT) is transforming the financial industry and leading to a rise in the modern banking system. Like in developed nations, disruptive technology is necessary to advance the traditional banking system in emerging economies. The present study aims to investigate the critical factors that influence a user's intention to accept blockchain technology for financial institutions. The proposed model is based on Technology Acceptance Model (TAM) constructs with trust and cost-saving, tested using structural equation modelling. Findings from an online survey of 188 practitioners working in Malaysia's financial sector confirm that all constructs except trust on perceived usefulness were found to have a significant impact during the blockchain implementation. Moreover, cost-saving matters most during the disruptive technology adoption for financial institutions. Based on the findings, the subsequent theoretical and practical implications are assessed, albeit with notable limitations.